1997
DOI: 10.1118/1.597962
|View full text |Cite
|
Sign up to set email alerts
|

A sector‐integration method for calculating the output factors of irregularly shaped electron fields

Abstract: Articles you may be interested inFinal Aperture Superposition Technique applied to fast calculation of electron output factors and depth dose curves Med. A practical method for the calculation of multileaf collimator shaped fields output factors Med. Phys. 26, 2385 (1999); 10.1118/1.598754 Monte Carlo investigation of electron beam output factors versus size of square cutout Med. Phys. 26, 743 (1999); 10.1118/1.598582Calculating output factors for photon beam radiotherapy using a convolution/superposition meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 16 publications
1
36
0
1
Order By: Relevance
“…Khan et al [9] reported a method for predicting ROF with irregular field using lateral build-up ratio concept. The sector integration concept [4,5,21], which is similar to Clarkson's model for calculation of the output factor for photon beams [22], has also been reported with accurate prediction of ROF. Even though we have not verified, sector integration similar to Khan et al [9] could be used with our equation and will be reported in a separate study.…”
Section: Cone Sizesmentioning
confidence: 96%
See 2 more Smart Citations
“…Khan et al [9] reported a method for predicting ROF with irregular field using lateral build-up ratio concept. The sector integration concept [4,5,21], which is similar to Clarkson's model for calculation of the output factor for photon beams [22], has also been reported with accurate prediction of ROF. Even though we have not verified, sector integration similar to Khan et al [9] could be used with our equation and will be reported in a separate study.…”
Section: Cone Sizesmentioning
confidence: 96%
“…This accuracy will be sufficient for double check of MUs in a clinical application and as such high energy electron beams with small fields are not often used. Previously several studies reported the use of polynomial functions for fitting to ROF curves [4,19]. Chow et al [20] reported an in-house software for ROF prediction using exponential approximation.…”
Section: Cone Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the methods for predicting cutout output factors for electron beams include the equivalent square,10, 11 square root,12 one‐dimensional,13 and sector‐integration methods 14. These algorithms predict the output factor of an irregular electron field using a database of parameters based on measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the empirical and theoretical models, there was a few published semiempirical models based on the sector integration concept. [13][14][15][16] The sector integration concept was similar to the one introduced by Clarkson 17 for the calculation of the output factor for photon beams. The original method by Jursinic and Mueller 14 has been further modified by Choi and co-workers 15,16 to allow for the calculation of ROF of irregular shaped electron fields in the case of extended source to surface distance.…”
Section: Introductionmentioning
confidence: 99%